Development and Evaluation of Affective Domain Using Student’s Feedback in Entrepreneurial Massive Open Online Courses - Wu, Wen-Hsiung; Kao, Hao-Yun; Wu, Sheng-Hsiu; Wei, Chun-Wang (Frontiers in Psychology, 2019)
Entrepreneurship education is a very important issue in the digital age. It aims to enable learners and society to respond to emergent economic and employment challenges. When entrepreneurs struggle to launch and sustain a new venture, the key question usually is not a lack of relevant knowledge, but the necessary fortitude and attitude to face down difficulties and challenges. Thus, entrepreneurs require development in the affective domain. However, most of courses emphasize the cognition and psychomotor functions, but neglects the affective domain. This study attempts to combine entrepreneurial MOOC courses and blended curriculum design for affective learning. A total of 32 students participated a nine-week social entrepreneurship program. Content analysis was used for comparison of the learning performance. The findings suggest that social entrepreneurship courses can be effectively used to help learners achieve learning objectives of different affective levels, but this is a time-intensive process, particularly for higher levels. The affective development of the final level takes longer to achieve; therefore, course designers should adopt a spiral structure which frequently revisits concepts in the last three levels. Moreover, MOOC courses are designed for mass usage, and treat all learners uniformly. MOOCs course content should be supplemented and adjusted according to specific course goals and student needs.